The habitus and technological practices of rural students: a case study - Laura Czerniewicz; Cheryl Brown (South African Journal of Education, 2014)
This paper describes the habitus and technological practices of a South African rural student in his first year at university. This student is one of five self-declared rural students, from a group of 23 first-years in four South African universities, whose access to, and use of, technologies in their learning and everyday lives was investigated in 2011 using a 'digital ethnography' approach. Their digital practices, in the form of their activities in context, were collected through multiple strategies in order to provide a nuanced description of the role of technologies in their lives. The student reported on here came from a school and a community with very little access to information and communication technologies (ICTs). While the adjustment to first year can be challenging for all students, the findings show that this can be especially acute for students from rural backgrounds. The study provides an analysis of one student's negotiation of a range of technologies six to nine months into his first year at university. Earlier theoretical concepts provide a lens for describing his practices through a consideration of his habitus, and access to and use of various forms of capitals in relation to the fields - especially that of higher education - in which he was situated.